1978
DOI: 10.1152/jappl.1978.44.4.596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of five human anesthetics on respiratory control in cats

Abstract: The effect of halothane, fentanyl, Innovar, thiopental, and ketamine on inspiratory output, vagal influence, and chest wall reflex was assessed in seven cats lightly anesthetized with pentobarbital, using the method of airway occlusion with and without rapid vagal cooling. All anesthetics depressed inspiratory output, as expressed by deltaP/deltat, of the first occluded inspiration. However, only halothane depressed peak inspiratory output (Pmax). Phasic vagal influence was markedly depressed by 2% halothane b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…Younes and Youssef [20] reported that the phasic vagal influence was depressed markedly at 2% halothane, which equates to 2.3 MAC of halothane, supporting our results.…”
Section: Discussionsupporting
confidence: 91%
“…Younes and Youssef [20] reported that the phasic vagal influence was depressed markedly at 2% halothane, which equates to 2.3 MAC of halothane, supporting our results.…”
Section: Discussionsupporting
confidence: 91%
“…This is because reflexes from the chest wall that have effects on TI are quite weak and tend to shorten TIn when the mechanical load is increased (21,22), whereas what we observed was a reduction in TIn as the mechanical load was decreased through an increase in ventilator flow.…”
Section: Response Of Neural Inspiratory Durationcontrasting
confidence: 67%
“…For example, opioids enhance HeringBreuer reflex-mediated slowing of respiration (5, 7, 9, 12, 21, Rhythmic membrane depolarization and hyperpolarization in the neuron, along with PNA, are slowed by fentanyl, and neuron input resistance is increased during all phases of the respiratory cycle. 61), but the effect is due solely to prolongation of the expiratory phase, and, in the present study, the reflex was eliminated by bilateral cervical vagotomy before fentanyl was tested. Respiration is also slowed when N-methyl-D-aspartate (NMDA) receptors are pharmacologically blocked and vagal pulmonary feedback to the central nervous system is prevented (13,57).…”
Section: Discussionmentioning
confidence: 39%